Correlation of fornix damage with memory impairment in six cases of colloid cyst removal. - McMackin, D; Cockburn, J; Anslow, P; Gaffan, D (1995)
We studied six patients in whom colloid cysts had been removed surgically from the third ventricle. The patients were selected simply by availability for the study, not on grounds of clinically diagnosed amnesia or its absence. The outcomes of operation ranged from one patient who had postoperatively resumed a normal life without complaint of memory disorder at any stage, through four who complained of memory disorder since operation, to one who was so severely amnesic as to require constant supervision. Each patient was given psychometric tests of memory, and was also scanned by magnetic-resonance imaging. One of us examined the six scans and assessed the extent of damage to the fornix, and any other brain damage, in ignorance of the outcomes of the psychometric tests. The fornix in the right hemisphere had been destroyed in all six cases, and all showed evidence of moderate or severe impairment in nonverbal memory. The fornix in the left hemisphere was intact in only one patient; this was the patient who had resumed a normal life without complaint of memory disorder. The left fornix was damaged with some sparing in one further patient, and the remaining four patients showed destruction of the fornix in the left as well as in the right hemisphere. The severity of impairment in verbal memory in these six cases was related to the severity of the damage to the left fornix. No other evidence of brain damage appeared to be systematically related to memory ability. These results add to the evidence that bilateral fornix damage produces amnesia, and that sparing of the left fornix alone is sufficient to ensure a more favourable outcome.